ANALISIS PERUBAHAN PENGGUNAAN LAHAN BERDASARKAN HASIL INTERPRETASI VISUAL CITRA SATELIT (Studi Kasus: Kecamatan Karangploso, Kabupaten Malang) - Nevi Anggraeni Priyono; Yuni Agung Nugroho; Toto Suharjanto (Badan Penerbitan Universitas Widyagama Malang, 2021)
ABSTRAKPerkembangan jaman berdampak pada perubahan penggunaan lahan yang ada di Kecamatan Karangploso. Hal ini terjadi karena perkembangan jumlah penduduk yang begitu pesat, sehingga kebutuhan akan tempat tinggal, dan tempat berusaha juga meningkat. Pesatnya jumlah populasi penduduk ini mengakibatkan tingginya perubahan penggunaan lahan. Oleh karena itu tujuan penelitian adalah untuk mengetahui besar perubahan penggunaan lahan di Kecamatan Karangploso pada rentang waktu 2008-2018, termasuk lahan pertanian. Teknik analisis data dalam penelitian ini menggunakan analisis citra satelit, yaitu menganalisis perubahan penggunaan lahan tahun 2008 dan 2018 dengan membandingkan klasifikasi penggunaan lahan. Hasil penelitian menunjukkan bahwa selama sepuluh tahun terakhir terjadi perubahan penggunaan lahan. Lahan yang mengalami penambahan luasan paling besar terutama adalah lahan yang berada di Desa Donowarih yaitu sebesar 21.17% pada periode 2008-2011. Lahan yang semula seluas 136.85 ha bertambah menjadi 1036.90 ha. Lahan yang mengalami penurunan luasan paling besar adalah lahan sawah berpengairan diusahakan yaitu sebesar 22.26%, yang semula dengan luas 1036.90 ha turun menjadi 80.0 ha. Penelitian ini diharapkan dapat digunakan untuk penataan wilayah di Kecamatan Karangploso, sehingga pihak-pihak yang berwenang dalam perencanaan penataan wilayah dan pembuat kebijakan dapat memberi keputusan yang tepat untuk membangun wilayah tersebut agar dapat tertata dengan baik dan bisa berkembang secara berkelanjutan. Kata kunci: penggunaan lahan, penginderaan jauh, sistem informasi geografis, karangploso ABSTRACTThe development of the era has an impact on changes in land use in Karangploso District. This is due to the rapid development of the population, so the need for housing and places of business has also increased. The rapid population growth has resulted in high changes in land use. Therefore, the purpose of the study was to find out how much land use change in Karangploso District was in the 2008-2018 period, including agricultural land. The data analysis technique in this study uses satellite imagery analysis, namely analyzing land use changes in 2008 and 2018 by comparing land use classifications. The results showed that during the last ten years there was a change in land use. The land that experienced the largest increase in area was mainly land in Donowarih Village, which was 21.17% in the period 2008-2011. The original land area of 136.85 ha was increased to 1036.90 ha. The land that experienced the greatest decrease in area was cultivated irrigated rice fields, which was 22.26%, which was originally with an area of 1036.90 ha and decreased to 80.0 ha. It is hoped that this research can be used for regional planning in Karangploso District, so that the authorities in regional planning planning and policy makers can make the right decisions to develop the area so that it can be well organized and can develop sustainably. The development of the era has an impact on changes in land use in Karangploso District. This happens because of the rapid development of the population, so the need for a place to live and a place to do business will increase. The rapid population growth results in high changes in land use. Therefore, the purpose of the study was to find out the number of land use change in Karangploso District in the 2008-2018 period. The data analysis technique in this study uses satellite imagery analysis, namely analyzing land use changes in 2008 and 2018 by comparing land use classifications. The results show that during the last ten years, there was a change in land use. Land which has increased the largest especially in Donowarih village was 21.17% in the 2008-2011. Land which was originally 136.85 ha became 1036.90 ha. The land that has decreased the greatest decrease in area was cultivated rice fields, which was 22.26%, which was originally 1036.90 ha icreased to 80.0 ha.This research is expected to be used for regional planning in Karangploso District, so that the authorities in the planning of regional structuring and those who make policies can give the right decisions to develop the area so that it can be well organized and develop sustainably.